PALEOCENE SEDIMENTS OF THE WESTERN PART OF THE BLACK SEA MEGADEPRESSION: LITHOFACIES, CONDITIONS OF SEDIMENTATION, DYNAMICS OF THE DEVELOPMENT OF OIL AND GAS SYSTEMS - HRYHORCHUK, Kostyantyn; HNIDETS, Volodymyr (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Based on the results of lithogenetic studies of the Paleocene sediments of the western part of the Black Sea megadepression, the main features of the litho-facies zonation in individual layers have been established. It is shown that the role of limestones in the section significantly increases from Danish to Zeeland deposits, with the formation of an extensive carbonate field in the eastern part of the studied area in the latter case. Marls are characterized by background development with an inherited maximum in the area of well Flangova-2 and a branch in the direction of the Odesa (Zelandian stage) and Hamburtsev (Tanet stage) structures. Argillites are distinguished by their minimal development in the Zeeland deposits, as well as by the change in the orientation of the range of their elevated contents from submeridional in the Danish layer to sublatitudinal in the Thanet layer. The reconstruction of the conditions of sedimentation was carried out, in particular, the spatial and age features of the distribution of biogenic accumulative bodies were determined. In Danish times, biogenic bodies were localized in the Bezymenno-Odeska, Golitsyn-Shmidtivska, and Shtormov-Arkhangelsk areas. In Zelandsky, the area of development of such formations on the southern side of the trough has significantly increased with the formation of a large bioherm massif, which included the following structures: Hamburtsev, Stormov, Arkhangelsky, Krymsk, Central. During the Thanetian time, the eustatic rise of the sea level caused an increase in the area of distribution of the outer shelf sediments in the axial zone of the depression and migration (within the northern side of the depression) of the zone of development of biogenic bodies in the northern direction. On the southern side, as a result of the sedimentation development of the Black Sea-Kalamite uplift, bioherms developed. A certain difference in the mode of catagenesis on different structures has been established. On the basis of the created generation and migration models, the different timing of the formation of deposits of the Odesa, Golitsyn, and Storm deposits (Oligocene and Miocene) is argued. The possibility of modern replenishment of their reserves due to the arrival of hydrocarbons from intermediate reservoirs is shown. Lithogenetic reasons for the low prospects of deposits of the Hamburtsev structure were grounded. The lithophysical structure of the Paleogene deposits was clarified and a number of oil and gas prospective objects were located.